Unplugged Robotics as a Platform for Cybersecurity Education in the Elementary Classroom (Journal of The Colloquium for Information Systems Security Education, 2019)
Robotics may be an ideal way to teach cybersecurity concepts to young students in the elementary classroom. Research shows robots can be an engaging experience and benefit learning in ways useful in other areas of education. Programming robots provides an ideal context for compelling demonstrations of cybersecurity concepts. Unplugged robotics activities benefit from the engaging aspect of robots but have the added advantage of bypassing hardware and making some concepts more transparent. Sen?or Robot is a gamified unplugged robotics activity modeled after some activities used before but specifically designed for cybersecurity education in the context of mathematics. The design and implementation of Sen?or Robot in a third-grade classroom is discussed along with observations and results of student assessments. Strengths and weaknesses of Sen?or Robot are examined and guide a proposed revision of the game called Frogbotics. An expanded instruction set and applicability to English language arts are considered along with ways to use Frogbotics to teach specific topics in cybersecurity. A website is provided as a dissemination point for materials developed in the study.
Keywords: computer science; cybersecurity; education; elementary; Frogbotics; K-12; programming; robotics; Señor Robot; unplugged